Are less developed countries more exposed to multinational tax avoidance? Method and evidence from micro-data - Niels Johannesen; Thomas Tørsløv; Ludvig Wier (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
We use a global dataset with information on 210,000 corporations in 102 countries to investigate whether cross-border profit shifting by multinational firms is more prevalent in less developed countries. We propose a novel technique to study aggressive profit shifting and improve the credibility of existing techniques. Our results consistently show that the sensitivity of reported profits to profit-shifting incentives is negatively related to the level of economic and institutional development. This may explain why many developing countries opt for low corporate tax rates in spite of urgent revenue needs and severe constraints on the use of other tax bases.
Keywords: H25; H26; H87; O23; 330; developing countries; international taxation; multinational firms; profit shifting; tax avoidance; tax evasion